Kajian Variasi Od Tube Heat Exchanger Shell & Tube terhadap Temperatur dan Laju Perpindahan Panas dengan Heat Transfer Research Inc - Aji Abdillah Kharisma; Rangga Triatmaja (Universitas Sriwijaya, 2022)
The metal slab production process requires a machine that works continuously. The machine used in the production of the metal slab is a hot strip mill which is run by a hydraulic system. The plate production process takes a long time, causing high heat temperatures in the machine, therefore it is necessary to require a heat exchanger to prevent excessive overheating. In this research, a study of the shell & tube heat exchanger will be carried out from the variation of the OD tube to the output to be produced, namely the heat transfer rate. The type of flow used is counterflow, double segmental baffle, two-pass tube passes with water fluid from the cooling tower on the tube side and oil fluid on the shell side and the design variations of the OD tube made are 19,050 mm, 22,225 mm, and 25,400 mm in the HTRI software.